Presidential decree-law no 58/2014 concerning the cancellation of decree- law no 102/2012 amending some provisions of the general sales tax law no.11/1991 and the amendment of certain provisions of the general sales tax law = قرار رئيس جمهورية مصر العربية بالقانون رقم 58 لسنة 2014 بإلغاء القرار بقانون الضريبة العامة على المبيعات الصادر بالقانون رقم 11 لسنة 1991 وتعديل بعض أحكام قانون الضريبة العامة على المبيعات - Egypt : Ministry of Finance. The Egyptian Customs Authority (2025)
presidential decree-law no. 58 of the year 2014 concerning the cancellation of decree- law no 102 of the year 2012 amending some provisions of the general sales tax law no.11 of the year 1991 and the amendment of certain provisions of the general sales tax law قرار رئيس جمهورية مصر العربية بالقانون رقم 58 لسنة 2014 بإلغاء القرار بقانون الضريبة العامة على المبيعات الصادر بالقانون رقم 11 لسنة 1991 وتعديل بعض أحكام قانون الضريبة العامة على المبيعات